Gender Bias in Intrahousehold Allocation: Evidence from an Unintentional Experiment - Braido, Luis H. B.; Olinto, Pedro; Perrone, Helena (The Review of Economics and Statistics, 2012)
We use data from a Brazilian social program to investigate the existence of gender bias in intrahousehold allocations of resources. The program makes cash transfers to mothers and pregnant women in poor households. Bureaucratic mistakes, beyond the control of the applicants, have inadvertently excluded many households that had applied and were accepted to the program. This unintentional natural experiment is used to identify the impact of an exogenous variation in female nonlabor income over household consumption. We find that program participation led to an increase in food expenditure, but this effect is not due to women being the benefit recipients.